The Israeli peace movement : a shattered dream - Hermann, Tamar (New York : Cambridge University Press, 2009)
'This books deals with the predicament of the Israeli peace movement, which, paradoxically, following the launching of the Oslo peace process between Israel and the Palestinians in 1993, experienced a prolonged, fatal decline in membership, activity, political significance, and media visibility. After presenting the regional and national background to the launching of the peace process and a short history of Israeli peace activism, the book focuses on external and internal processes and interactions experienced by the peace movement, after some basic postulates of its agenda were actually, although never explicitly, embraced by the Rabin government. The analysis brings together insights from social movement theory and theories on public opinion and foreign and security policymaking. The book's conclusion is that, despite its organizational decline and the zero credit given to it by the policymakers, in retrospect it appears that the movement contributed significantly to the integration of new ideas for possible solutions to the Middle East conflict in the Israeli mainstream political discourse'--Provided by publisher.
Exploring peace activism: a road map -- Mapping the Israeli socio-political terrain -- Paving the road to Oslo: Israeli peace activism through 1993 -- The path strewn with obstacles (1993-2008) -- Exploring new ways or getting lost? -- Appendix 1: List of Israeli peace groups -- Appendix 2: Israeli Jewish public opinion on the Oslo process, 1994-2008.
Includes bibliographical references (p. 279-303) and index.
Keywords: Peace movements -- Israel -- History; Arab-Israeli conflict -- History